Analysis on Vibration Influence Factors of Hybrid Permanent Magnet Governor Rotor - Changsheng ZONG; Qingzhong GAO; Yutong HE; Bai YANG (发电技术)
In order to study the effect of the conductor rotor of a hybrid PMG with radial and axial magnetic circuits on the vibration of the hybrid PMG, firstly, a rotor simulation model of the hybrid permanent magnet governor was established and the vibration reasons of the hybrid permanent magnet governor were analyzed. Secondly, based on Donnell's shell theory, a hybrid PMG conductor rotor model was established. Finally, finite element software was used to complete the vibration simulation analysis of the PMG conductor rotor. The results show that the higher the thickness difference between the axial and radial conductor rotors, the worse the vibration effect of the conductor rotors. The radial conductor rotor can suppress the vibration of the axial conductor rotor. The vibration effect of the conductor rotor is proportional to the thick-diameter ratio and inversely proportional to the length-diameter ratio.